2016
DOI: 10.1016/j.jcv.2016.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatitis and cholecystitis in primary acute symptomatic Epstein-Barr virus infection – Systematic review of the literature

Abstract: Acute pancreatitis and acalculous cholecystitis have been occasionally reported in primary acute symptomatic Epstein-Barr virus infection. We completed a review of the literature and retained 48 scientific reports published between 1966 and 2016 for the final analysis. Acute pancreatitis was recognized in 14 and acalculous cholecystitis in 37 patients with primary acute symptomatic Epstein-Barr virus infection. In all patients, the features of acute pancreatitis or acalculous cholecystitis concurrently develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
46
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 52 publications
2
46
2
2
Order By: Relevance
“…3 After a thorough search in the literature we found two reports of acute hepatitis A associated with pancreatitis and cholecystitis, 18,19 two cases of acute non-fulminant viral hepatitis E, presenting with acute pancreatitis 20,21 and a systematic review about Epstein-Barr virus infection causing pancreatitis and cholecystitis. 22 In the present case, we observed a rare occurrence of acute viral hepatitis B associated with acute pancreatitis and acute cholecystitis, which also had clinical improvement with conservative management. We believe that this association may be underdiagnosed, mainly due to its oligosymptomatic presentation.…”
Section: Discussionsupporting
confidence: 50%
“…3 After a thorough search in the literature we found two reports of acute hepatitis A associated with pancreatitis and cholecystitis, 18,19 two cases of acute non-fulminant viral hepatitis E, presenting with acute pancreatitis 20,21 and a systematic review about Epstein-Barr virus infection causing pancreatitis and cholecystitis. 22 In the present case, we observed a rare occurrence of acute viral hepatitis B associated with acute pancreatitis and acute cholecystitis, which also had clinical improvement with conservative management. We believe that this association may be underdiagnosed, mainly due to its oligosymptomatic presentation.…”
Section: Discussionsupporting
confidence: 50%
“…1 Less common and atypical complications include splenic rupture, 2 myopericarditis, 3 acute kidney injury (most commonly acute interstitial nephritis), 4 pancreatitis and acalculous cholecystitis. 5 PTA is a common complication of bacterial tonsillitis but a rare complication in infectious mononucleosis. 6 The pathogenesis of this complication in the setting of infectious mononucleosis is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Thickened gallbladder wall was the most consistent finding in all cases, ranging from 4.2 to 15 mm thickness. In 2016, a literature review performed by Kottanattu et al [7] identified 37 cases of AAC caused by EBV. Thirty-two of the patients were female and five of the patients were male.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-two of the patients were female and five of the patients were male. These cases recovered conservatively without surgery or corticosteroids [7]. Upon a literature review, at least 12 cases of AAC caused by EBV have been reported since the year 2016 [4,[8][9][10][11][12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%